NCOG-54. SAFETY OF TRANSSPHENOIDAL SURGERY FOR NONFUNCTIONING PITUITARY ADENOMA IN ELDERLY PATIENTS. (9th November 2020) - Pereira, Matheus; Oh, Taemin; Joshi, Rushikesh; Haddad, Alexander; Pereira, Kaitlyn; Osorio, Robert; Donohue, Kevin; Peeran, Zain; Sudhir, Sweta; Jain, Saket; Beniwal, Angad; Gurrola, José; et al.
Abstract: INTRODUCTION: Life expectancy has increased over the past century, shifting the demographic distribution towards older age groups. Elderly patients comprise up to 14% of patients with pituitary tumors, with most lesions being nonfunctioning adenomas (NFPAs). Here, we compare clinical and surgical outcomes and post-operative complications between non-elderly adult (age ≥ 18 years and ≤ 65 years) and elderly (age > 65 years) NFPA patients. METHODS: Retrospective review of 908 patients undergoing transsphenoidal surgery for NFPA at a single institution from 2007-2019. RESULTS: Elderly patients represented 32.4% of patients. Both groups were similar in gender (57.3% vs 60.5% male;P=0.4), tumor size (2.56 vs 2.46 cm;P=0.2), and cavernous sinus invasion (35.8% vs 33.7%;P=0.6). Regarding post-operative outcomes, length of stay (1 vs 2 days; P=0.5), extent of resection (59.8% vs 64.8% GTR;P=0.2), CSF leak requiring surgical revision (4.3% vs 1.4%;P=0.06), 30-day readmission (8.1% vs 7.3%;P=0.7), infection (3.1% vs 2.0%;P=0.5), and new hypopituitarism (13.9% vs 12.0%;P=0.3) were similar between both groups. Elderly patients were less likely to have adjuvant radiation (8.7% vs 16.3%;P=0.009), future re-operation (3.8% vs 9.5%;P=0.003), and post-operative diabetes insipidus (DI) (3.7% vs 9.4%;P=0.002), and more likely to have post-operative hyponatremia (26.7% vs 16.4%;P< 0.001) and new cranial nerve deficit (1.9% vs 0.0%;P=0.01). Elderly patients' post-operative sodium peaked and troughed on POD3 (mean=138.7 mEq/L) and POD9 (mean=130.8 mEq/L), respectively, compared to non-elderly patients (peak POD2 mean=139.9 mEq/L, trough POD8 mean=131.3 mEq/L). CONCLUSION: Our analysis revealed that elderly patients experienced more post-operative hyponatremia, while non-elderly patients experienced more post-operative DI. Elderly patients also experience later peak and trough in serum sodium, suggesting age-related differences in stalk-related morbidities of NFPA resection. Overall, our results show that transsphenoidal surgery for NFPA in elderly patients is safe with low complication rates. We hope our results will guide discussions with elderly patients regarding possible risks and outcomes.